(untitled) (Journal of the College of Basic Education, 2022)
The study was conducted in the plant pathology laboratories of the College of Agriculture / University of Baghdad and Jisr Al-Musayyib Company, with the aim of molecular investigation of the potato virus (Potato Virus M) on potato plants (Solanum tuberosum) in the central region of Iraq, and the technology of reverse transcriptase was adopted. - polymerase chain reaction) based on the primers Car f1, Carla cp, Carla uni, Uligo dt, M4t, PVM (F) and PVM (R) and the double antibody sandwish enzyme-linked immunosorbent assay, in which a specialized anti-potatovirus serum was used. (PVM).